2022
DOI: 10.3389/fsurg.2022.943544
|View full text |Cite
|
Sign up to set email alerts
|

The role of bariatric and metabolic surgery in the development, diagnosis, and treatment of endometrial cancer

Abstract: The obesity pandemic continues to contribute to a worsening burden of disease worldwide. The link between obesity and diseases such as diabetes, cardiovascular disease, and cancer has been well established, yet most patients living with obesity remain untreated or undertreated. Metabolic and bariatric surgery is the most effective and durable treatment for obesity, is safe, and may have a protective benefit with respect to cancer incidence. In this review, an overview of the link between obesity, metabolic sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 105 publications
(119 reference statements)
0
10
0
Order By: Relevance
“…AUB is the most common presentation for endometrial cancer, which is one of the most closely associated malignancies to obesity [3 ▪ ,28]. A retrospective cohort study published in 2022 that examined the risk factors for endometrial hyperplasia or malignancy found that BMI was more predictive of endometrioid intraepithelial neoplasm or malignancy than age in premenopausal women [29 ▪ ].…”
Section: Discussionmentioning
confidence: 99%
“…AUB is the most common presentation for endometrial cancer, which is one of the most closely associated malignancies to obesity [3 ▪ ,28]. A retrospective cohort study published in 2022 that examined the risk factors for endometrial hyperplasia or malignancy found that BMI was more predictive of endometrioid intraepithelial neoplasm or malignancy than age in premenopausal women [29 ▪ ].…”
Section: Discussionmentioning
confidence: 99%
“…Authors have demonstrated that weight loss can decrease the recurrence of EC [ 79 ]. Investigators are starting to assess interest and utility in bariatric surgery as a tool for weight loss and its impact on HT for EC among young patients ( Table 1 , NCT04008563) [ 80 ]. Obesity is also an independent risk factor for infertility, [ 81 ] as well as a known risk factor in pregnancy [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent meta-analysis showed that several recent retrospective cohort studies consistently demonstrate a reduction in cancer incidence among those who undergo metabolic surgery. 78,79 There are several potential ways by which weight loss may positively impact outcomes in endometrial cancer. First, epidemiologic data support a protective biological role for weight loss.…”
Section: Weight Loss As An Intervention For Endometrial Cancermentioning
confidence: 99%
“…Endometrial cancer has a strong association with obesity, and data indicate that weight loss may reduce this risk. For example, a recent meta‐analysis showed that several recent retrospective cohort studies consistently demonstrate a reduction in cancer incidence among those who undergo metabolic surgery 78,79 . There are several potential ways by which weight loss may positively impact outcomes in endometrial cancer.…”
Section: Frontiers In Immunometabolismmentioning
confidence: 99%